Knowledge graph and bibliometric analysis of inflammatory indicators in ovarian cancer - Zhang, Liyan; Guo, Linlin; Wang, Haiyan; Yang, Huan; Dong, Jiarui (Frontiers in Oncology, 2025)
BackgroundChronic inflammation is a type of inflammatory response that lasts for a relatively long period of time. Occurrence and development of many diseases are closely related to chronic inflammation. In the process of the occurrence of certain tumors, chronic inflammation also plays an important role. For example, chronic inflammation of the stomach caused by chronic Helicobacter pylori infection is an important risk factor for gastric cancer. Inflammatory cells can release reactive oxygen species (ROS), cytokines and so on which can induce DNA damage in cells, activate oncogenes and suppress tumor suppressor genes, thus promoting the proliferation, survival, migration and invasion of tumor cells. Recent studies have shown that great progress has been made in understanding the role of chronic inflammation in ovarian cancer. However, there has been no bibliometric analysis in this research field yet. The aim of this study is to review the knowledge structure and research hotspots of inflammatory indicators in ovarian cancer through bibliometric methods.MethodsA computer search was conducted on 595 articles related to inflammatory markers and ovarian cancer in the Web of Science Core Collection (WoSCC) database from 2000 to 2024. Relevant software such as VOSviewer, CiteSpace, R package “bibliometrix” and Microsoft Office Excel 2019 were used to conduct a comprehensive bibliometric analysis on these related articles and analyze the research status and development directions over the past more than 20 years.ResultsA total of 595 articles related to inflammatory markers and ovarian cancer were included in this study. Among them, the United States and China had the largest number of published articles. Global publications have been steadily increasing every year with reaching a peak in 2023. The United States had the largest number of publications and followed by China and Italy. Among them, Harvard University in the United States had the largest number of published papers, approximately 100 and followed by the National Institutes of Health (NIH) and the NIH National Cancer Institute (NCI) with 52 each. CHATURVEDI AK ranked first in the total citation number of published articles, with a total of 683 citations and HILDESHEIM A ranked second in the total citation number, with a total of 651 citations. The number citations are highlighting their significant contributions to this field. The two magazines of the CANCER EPIDEMIOLOGY BIOMARKERS & PREVENTION and JOURNAL OF OVARIAN RESEARCH had the most published articles and followed by Cancer and PLOS ONE. The article “COUSSENSLU, 2002, NATURE V420, P860, 00110, 1030/NATURE01322” was the most frequently cited one, with 46 citations. The article “CRVENNKOY SL2010, CELL7140 2883, 00110 016402LL 201001025” was cited 38 times and ranked second. The analysis results of CiteSpace show that ovarian cancer, inflammation and prognosis are identified as the keywords with the highest frequencies, indicating the core research focuses and directions in this area. The results of the research topics in this area show that from 2019 to 2024, the main themes were ovarian cancer, inflammation and so on. Through the analysis of the research trends, it can be known that from 2019 to 2024, ovarian cancer and inflammation were the main trends, which is the analysis of trend topics. All in all, the indicators of ovarian cancer and inflammation represent the frontier research directions in this field.ConclusionThis is the first bibliometric study that comprehensively summarizes the research trends and progress of inflammatory indicators in ovarian cancer. The information in this study has summarized the recent research frontiers and hotspots. The results will provide references for scholars to study the early diagnosis and treatment of inflammatory indicators and ovarian cancer.